Politics in banking: does political party control impact bank risk and return?. Issue 2 (12th February 2018) - Fayman, Alex; He, Ling T.; Casey, K. Michael
Abstract : Purpose: The purpose of this paper is to investigate the potential impact of political party control on bank profitability and risk. This study extends previous work by looking at overall political power with respect to party control of the House, Senate, and the Presidency. Design/methodology/approach: This paper employs regression analysis using several different dependent measures of risk and return. The independent variables include dummies to represent political power and control. Findings: The results indicate that political control does impact both bank returns and risk. More specifically, concentration of power in either party results in higher profits. However, risk and returns typically increase during periods of democratic control. Originality/value: To date, no research addresses the impact of political control and party affiliation on bank risk and return. Given the importance of banks to the overall economy and financial system, this research should provide policymakers and regulators with a different perspective on bank risk and return.